FIRST INTERNATIONAL CODE OF ETHICS FOR NURSES. - Taka Oguisso; Magali Hiromi Takashi; Fernandes de Freitas, Genival; Barrionuevo Bonini, Bárbara; Araújo da Silva, Thaís (Texto & Contexto Enfermagem, 2019)
Objective: to historicize the approval of the First International Code of Ethics for Nurses and analyze its 14 articles and their relevance to the historical and current context. Method: this is a historical and social study, with a qualitative approach. The sources were composed of official publications of the International Council of Nurses and reports of activities developed during the X Quadrennial Congress in 1953. A document review was carried out, involving two processes: the external criticism, regarding the authenticity of the document, and the internal criticism, which consists in the careful reading of the text, in an effort to interpret it. Results: the first International Code of Ethics for Nurses discusses the nurses' responsibilities in their professional and personal life to guarantee the social recognition of this professional, as well as an ethical performance, encompassing the following aspects: the nurse's commitment to the care provided and the valuation of professional and personal relationships, involving physicians, patients, and the community. Conclusion: as this code would have to meet the needs of nurses in the several cultures, religions, customs, and laws and regulations of the continents, it was based on universal principles and concepts, such as respect for life, dignity and human rights, without discrimination of any kind. In this direction, the 1st International Council of Nurses Code of Ethics set out to be a universally accepted document in its fundamental ethical principles, regarding the patient and the relationships between the nursing team, and physicians, as well as other professionals.